TI_GERICHTE 11.2016.51 vom 16. Mai 2018 , Ipoteca legale degli artigiani e degli imprenditori: iscrizione definitiva - TI Tribunale d'appello (2018)
Ipoteca legale degli artigiani e degli imprenditori: iscrizione definitiva